Effects of Stroking on Salivary Oxytocin and Cortisol in Guide Dogs: Preliminary Results - Asahi Ogi; Chiara Mariti; Paolo Baragli; Valeria Sergi; Angelo Gazzano (Animals, 2020)
This pilot study aimed at investigating how salivary oxytocin levels are affected by human interaction and isolation in eight guide dogs (six Labrador retrievers and two golden retrievers; four males and four females, 21.87 ± 1.36 months old) just before assignment to the blind person. Each dog engaged, at one-week intervals, in a positive (5 min of affiliative interaction with their trainer) and a negative (5 min of isolation) condition. Saliva samples used for Enzyme Immunoassay (EIA) quantification of salivary oxytocin were collected before and immediately after both experimental conditions. In order to assess potential hypothalamic pituitary adrenal (HPA) axis activation that could have affected oxytocin levels, saliva samples were collected 15 min after both experimental conditions for EIA quantification of salivary cortisol and a behavioral assessment was performed during the negative condition. The results were compared using the Wilcoxon test (p < 0.05). Oxytocin concentrations showed a statistically significant increase after the positive interaction (p = 0.036) and no difference after the negative one (p = 0.779). Moreover, no difference (p = 0.263) was found between the cortisol concentrations after each experimental condition and no signs of distress were observed during the isolation phase. These preliminary findings support the hypothesis that stroking dogs has positive effects on their emotional state independently of hypothalamic pituitary adrenal axis activation.